SAT0557 A Clinical Study To Examine Thresholds of Joint Space Width and Joint Space Area for Identification of Knee Osteoarthritis. (15th July 2016) - Ljuhar, R.; Nehrer, S.; Norman, B.; Ljuhar, D.; Haftner, T.; Hladuvka, J.; Bui Thi Mai, M.; Canhão, H.; Branco, J.; Rodrigues, A.-M.; Gouveia, N.; Fahrleitner-Pammer, A.; et al.
Abstract : Background: Osteoarthritis (OA) is a degenerative, slowly developing joint disease and characterized by pain and functional disability. Although clinical indications of OA can vary among different definitions there is a general agreement that the disease is associated with cartilage narrowing and the development of osteophytes and sclerosis within the subchondral bone. However, there is no general consensus about the threshold below which the joint space width (JSW) and the respective joint space area (JSA) can be certain indicators for the state of OA. Objectives: Therefore this study evaluates these limits to reveal quantitative information about indicators of OA. Methods: The study included 226 standardized knee radiographs from 101 female patients with OA, and 125 controls. All images were acquired in PA direction and standardized positions. The minimum JSW and JSA were calculated by using the i3a software. 3 physicians assessed the 2D radiographs by using the Kellgren & Lawrence Score and assigned the images to either a Case or Control group. A knee was assigned to the Case group, if at least two physicians assessed it as being affected by OA. The JSW was defined as the vertical distance from the inferior femur condyle to the superior tibia condyle on both the medial and lateral compartment, obtained from 4 distinct points from each side. By building a spline curve between the points of each condyle, the upper and lower boundaries of the JSA are defined for each side, whereas the outer points define the horizontal boundaries. For the JSW and JSA, only the minimum value of each variable was taken into account. Results: Considering the minimum JSW, an odds ratio of 5.63 (CI: 3.17–9.99) with an accuracy of 70.35% and a sensitivity of 70.30% can be obtained. Every subject that has a minimum JSW below 3.4mm belongs to the Case group. With respect to the minimum JSA, the odds ratio is 3.60 with an accuracy of 65.49% and a sensitivity of 65.35%. Results also show that every subject with a minimum JSA below 50mm 2 is being considered to have OA. Conclusions: Based on this study it can be concluded that a JSW below 3.4mm and a JSA below 50mm 2 at the knee joint are strong indicators for OA. Thus, for clinical assessments it is suggested to consider these threshold values for diagnostic purposes. In further studies, symptomatic knee OA should be incorporated to verify whether minimum JSWs and JSAs can also be linked to symptomatic knee pain. Disclosure of Interest: R. Ljuhar Employee of: Braincon Technologies, S. Nehrer: None declared, B. Norman Employee of: Braincon Technologies, D. Ljuhar Employee of: Braincon Technologies, T. Haftner Employee of: Braincon Technologies, J. Hladuvka: None declared, M. Bui Thi Mai: None declared, H. Canhão: None declared, J. Branco: None declared, A.-M. Rodrigues: None declared, N. Gouveia: None declared, A. Fahrleitner-Pammer: None declared, H.-P. Dimai: None declared